2017
DOI: 10.15406/jhvrv.2017.05.00176
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpes Virus Type 8 among Female-Sex Workers

Abstract: The prevalence of Human Herpes Virus type 8 (HHV-8) varies from one region to another and by populations. The modes of transmission and risk factors associated with HHV-8 among heterosexual adults are still not clear. HHV-8 has been associated with high risk sexual behavior. Female-sex workers (FSWs) are a high-risk group and therefore more vulnerable to sexually transmitted infections (STIs) compared to women in the general population. This review aimed at determining the global distribution of HHV-8 among FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…Nonsexual transmission of HHV-8 may be the predominant route through which HHV-8 is transmitted in Kenya. A review from studies on HHV-8 among FSWs around the world observed that high risk behavior and STIs were not associated with HHV-8 infection by majority of studies evaluated; concluding FSWs did not play a major role in HHV-8 transmission hence heterosexual transmission [39]. We interpret our results as indicating that sexual transmission of HHV-8 occurs rarely in this population.…”
Section: Discussionmentioning
confidence: 55%
“…Nonsexual transmission of HHV-8 may be the predominant route through which HHV-8 is transmitted in Kenya. A review from studies on HHV-8 among FSWs around the world observed that high risk behavior and STIs were not associated with HHV-8 infection by majority of studies evaluated; concluding FSWs did not play a major role in HHV-8 transmission hence heterosexual transmission [39]. We interpret our results as indicating that sexual transmission of HHV-8 occurs rarely in this population.…”
Section: Discussionmentioning
confidence: 55%
“…HHV-8 seroprevalence differs in different populations or risk groups and geographical regions reaching up to 50% prevalence in sub-Saharan Africa. In Europe and United States, HHV-8 prevalence is low among the general population but some population, such as people living with HIV and MSM have seroprevalence rates that reach 33-40% [4,[6][7][8]. In the Mediterranean, the prevalence ranges between 10 and 40% and is 0-20% in most parts of Asia [9].…”
Section: Introductionmentioning
confidence: 99%